1983
DOI: 10.2220/biomedres.4.155
|View full text |Cite
|
Sign up to set email alerts
|

<b>CROSS-LINKING OF FIBRIN BY ACTIVATED FACTOR XIII STIMULATES ATTACHMENT, MORPHOLOGICAL CHANGES AND PROLIFERATION OF </b><b>FIBROBLASTS </b>

Abstract: The response of fibroblasts to the conversion of fibrinogen into fibrin was investigated to clarify the relationship between the conversion and wound healing. The formation of fibrin by thrombin little affected fibroblast attachment and morphology. In contrast cells rapidly attached and subsequently spread on fibrin cross-linked by activated Factor XIII. The introduction of cross-linking also stimulated cell proliferation. However neither enzyme had much effect on cellular behavior. These results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…It is of note that due to the amount of tissue available, the yield and quality of extracted RNA from the empty defect sites was significantly lower than the other treatment conditions. Runx2 is regarded as the key regulator of osteogenesis and has been shown to be essential for skeletal patterning during embryogenesis and the progression of osteoblast differentiation (Keller et al 1985, Kasai et al 1983, Marktl et al 1974, Le Nihouannen et al 2006, Ducy et al 1999. Calvarial cells harvested from Runx2-deficient mice have increased rates of cell proliferation, DNA synthesis and G1/S phase markers; the reintroduction of Runx2 restores normal cell cycling, emphasizing the importance of Runx2 for cell cycle regulation (Komori et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that due to the amount of tissue available, the yield and quality of extracted RNA from the empty defect sites was significantly lower than the other treatment conditions. Runx2 is regarded as the key regulator of osteogenesis and has been shown to be essential for skeletal patterning during embryogenesis and the progression of osteoblast differentiation (Keller et al 1985, Kasai et al 1983, Marktl et al 1974, Le Nihouannen et al 2006, Ducy et al 1999. Calvarial cells harvested from Runx2-deficient mice have increased rates of cell proliferation, DNA synthesis and G1/S phase markers; the reintroduction of Runx2 restores normal cell cycling, emphasizing the importance of Runx2 for cell cycle regulation (Komori et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was reversed by the addition of purified fibronectin before clotting, suggesting that the fibronectin needs to be covalently cross-linked to fibrin by transglutaminase. The importance of this enzyme has been demonstrated in vitro (4,14,33) where optimal growth on clots requires the presence of the enzyme. Individuals with an inherited deficiency of the enzyme display poor wound-healing (1,6).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the interactions be tween the cells and the surrounding extracel lular matrix can modulate morphology, re plication and biosynthetic activities [Holderbaum and Ehrhardt, 1986;Kasai et al, 1983], FXIIIa is known to covalently cross link various matrix proteins or some matrix proteins with cell-membrane-associated pro teins like fibronectin or actin. Previous stud ies from our laboratory demonstrated the ability of FXIIIa to confer cells deficient in attachment to type I collagen with adhesive properties to this substratum [Paye et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that the crosslinking of the fibrin clot by FXIII stimulated the adhesion and the growth of fibroblasts [Kasai et al, 1983]. FXIII also stimulates the proliferation of fibroblasts and tumor cells in vitro [Bruhn and Pohl, 1981;Bruhn et al, 1983] and enhances the fibronectin-mediated adhesion of cells to collagen I [Paye and Lapiere, 1986a], However, the migra tion of epithelial cells onto the granulation tissue is inhibited by FXIII [Hashimoto and Marks, 1984],…”
Section: Introductionmentioning
confidence: 99%